1967
DOI: 10.1126/science.157.3791.935
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Protein Synthesis in a Cell-Free System from Hypertrophied Skeletal Muscle

Abstract: Hypertrophy of the rat soleus muscle was induced by tenotomy of the synergistic muscles. Four days after the operation, the weight of the muscle had increased by 30 percent. The hypertrophied muscle had an increased concentration of DNA and RNA, when compared to the contralateral control soleus. Although the amount of myofibrillar protein increased during the 4-day period, the concentration of this component decreased. Microsomes prepared from hypertrophied muscle had an increased RNA concentration. The combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
30
0

Year Published

1969
1969
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 15 publications
3
30
0
Order By: Relevance
“…Although Goldberg et al (1975) found no change in protein synthesis of skeletal muscle after electrical stimulation in vitro, Peterson & Lesch (1972) observed an increased incorporation of amino acids into proteins of the papillary muscle of the heart after repeated stimulations. Also in keeping with the present study Hamosh, Lesch, Baron & Kaufman (1967) found increased rates of protein synthesis during work-induced hypertrophy of skeletal muscle.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although Goldberg et al (1975) found no change in protein synthesis of skeletal muscle after electrical stimulation in vitro, Peterson & Lesch (1972) observed an increased incorporation of amino acids into proteins of the papillary muscle of the heart after repeated stimulations. Also in keeping with the present study Hamosh, Lesch, Baron & Kaufman (1967) found increased rates of protein synthesis during work-induced hypertrophy of skeletal muscle.…”
Section: Discussionsupporting
confidence: 77%
“…The increase in RNA concentration in response to activity (Fig. 3) is in agreement with the higher RNA concentrations, RNA polymerase activities and rates of RNA synthesis in hypertrophying muscles (Hamosh et al 1967;Sobel & Kaufman, 1970;Jablecki, Hauser & Kaufman, 1973). Further, the initial stimulation of protein synthesis by the return of normal activity appears to be dependent upon the synthesis of new RNA, rather than merely a more efficient utilization of existing RNA molecules (Table 1).…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, this fat-mobilizing effect, which persists for a considerable time after the cessation of exercise (15,16), could play a role in the conservation of lean tissue by making available to muscle and organ cells more of the energy stored as fat. The greater lean body mass of the exercising animals, as compared with the sedentary, food-restricted controls, could also reflect stimuli for amino acid conservation and protein synthesis, such as a direct effect of exercise on muscle (18) and the anabolic effects of increased levels of growth hormone secretion secondary to the exercise (19). (5), using the formula of Entenman, Goldwater, Ayres, and Behnke (2), on eight obese subjects who were on a restricted food intake for 12 wk (61%).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the metabolic capacity of muscles is affected specifically by the type of exercise training [1][2][3]. Increased activity or over-loading by removing the synergists causes a compensatory hypertrophy [4][5][6][7][8][9][10][11]. Hypertrophy is also induced by the stretching of matured muscles in vivo [12,13] and cultured myotubes and fibroblasts [14][15][16][17].…”
mentioning
confidence: 99%